Aktivitas Antibakteri Infusa Akar Bajakah (Spatholobus Littoralis Hassk) Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Mega Pratiwi Irawan; Elin Suhaila (LPPM Universitas Abdurrab, 2023)
Infectious diseases such as skin infections, respiratory tract infections and digestive tract infections are diseases caused by pathogenic microbes such as Staphylococcus aureus. Treatment for infectious diseases is by administering antibiotics and exploiting plants for alternative medicine. Bajakah root (Spatholobus littoralis Hassk) which has medicinal properties and has been used in traditional medicine. The aim of this research was to determine the potential of bajakah roots in inhibiting the growth of Staphylococcus aureus. The research method used was to test the antibacterial activity of Bajakah root infusion using the dilution method by determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Bajakah root infusion was prepared with concentrations of 10 g/100 ml, 5 g/100 ml, 2.5 g/100 ml, 1.25 g/100 ml, 0.625 g/100 ml, 0.3125 g/100 ml, 0, 15625g/100ml. Research showed that the MIC test of Bajakah root infusion at various concentrations shows that turbidity due to the dark color of the infusion, so additional examination of the suspension using Gram staining was required. The results of Gram staining showed that the infusion at a concentration of 10; 5; 2.5 and 1.25 g/100 ml do not indicate the presence of bacteria. Meanwhile, the infusion concentration was 0.625; 0.3125 and 0.1625 g/100 ml contained bacteria. This shows that the MIC of Bajakah root infusion was 1.25 g/100 ml. MBC was carried out at a concentration of 10; 5; 2.5 and 1.25 g/100 ml however there ware colonies on solid media. It was indicated that MBC cannot be determined. The conclusion of this research is that Bajakah root infusion has activity to inhibit the growth of Staphylococcus aureus.